Histopathological study of the effect of using repeated doses of platelets-rich plasma on articular cartilage repair in Rabbits - Mustafa A. Khaleefa; Hasanain A. Emran (Iraqi Journal of Veterinary Sciences, 2022)
The present study was performed on platelet-rich plasma compound from animals engaged in this work, to be directly injected in the joint space of the affected stifle joint 5mm diameter full-thickness articular cartilage removal in the knee joint manually using the same instrument 5 mm drill to remove the cartilage, by different doses to evaluate its influence on articular cartilage repair. In this experiment, 28 adult rabbits were used. The same defect is created on the lateral condyle of the distal end of the femur. Three identical groups of animals were formed randomly. Group I was untreated. Group II was treated with a single dose of PRP (which was administered immediately after the creation of the defect), and group III was treated with two doses of PRP (the first dose was given immediately after the creation of the defect, and the second doses after 15 days of the first one. The histological examinations were recorded of four rabbits of each group, which were euthanized one and two months after treatment, and the assessment of cartilage tissue repair was checked. The control group showed destruction of articular cartilage at the site of the lesion with involvement of subchondral bone in both periods 30 and 60 days of examination, while specimens taken from groups II and III after 30 days showed a new tissue formation which is characterized as the homogenous extracellular matrix, with the proliferation of active chondrocytes. At the same time, slides on day 60 of treatment showed an increased number of newly formed chondrocytes and a clear line of demarcation between articular cartilage and subchondral bone, representing the tissue filling the gap had been created at the beginning of the experiment.